Legal Provisions on Grievances, Denunciations, and Dispute Resolution in Medical Examination and Treatment Activities – Current Status and Some Suggestions for Improvement - Tran, Linh Huan; Pham, Thi Hong Tam (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Currently, the Law on Medical Examination and Treatment has provided specific regulations on complaints, denunciations and dispute resolution in medical examination and treatment activities to serve the timely adjustment of related arising issues. However, besides the positive aspects achieved, there still exist a number of certain limitations and shortcomings, which significantly affect the legitimate rights and interests of relevant entities. This article aims to elucidate the legal provisions on grievances, denunciations, and dispute resolution in medical examination and treatment activities, highlighting the existing limitations and deficiencies in regulations and law enforcement on this matter. Consequently, it proposes some recommendations to enhance the legal framework concerning grievances, denunciations, and dispute resolution in the healthcare sector, thereby contributing to improving the quality of medical services in Vietnam.